Effectiveness of alveolar preservation techniques for prosthetic and impant-prosthetic rehabilitations - Orlando Guerra Cobian; Clara Sánchez Silot; Luis Hernández Pedroso; Sonia Felipe Torres (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: The preservation of the alveolar ridge reduces the bone loss which is produced after an extraction, although there is a great controversy between the role of a non-traumatic extraction and the grafting technique for width and height maintenance.  Objective: To determine the effectiveness of the different preservation techniques of alveolar ridge in patients with immediate dental extractions, and to identify the complications associated with this technique. Material and method: A comparative case-series study was conducted in 125 patients with specific inclusion criteria in the Faculty of Odontology of Havana, during the period from 2014-2016. The cases were divided at random into 5 equal groups and were subjected to 5 preservation procedures.  A clinical and image analysis was carried out before treatment, as well as at 9 months after surgery. The variables evaluated were topographic distribution, implemented technique, total alveolar width, and alveolar bone height and width. Associated complications were also identified. Results: Female patients (56, 8%) aged 40-45 (35, 2%) predominated in the study.  The upper incisive canal region was the most preserved (26, 4%). The use of autologous bone (mandibular branch) exhibited a better bone preservation with only 0,03±0,63mm loss in width, and 0,03±0,82 loss in height. The most reported complication was the dehiscence in three cases. Conclusions: The loss in alveolar bone height and width was lower in the cases in which grafting techniques or alloplastic materials were used than in the isolated non-traumatic extraction. The autologous bone graft of the mandibular branch exhibited the best preservation results, and there were low rates of associated complications. Keywords: alveolar preservation, autologous grafts, alloplastic grafts, alveolar atrophy, techniques, alveolar regeneration.